PERBEDAAN KUANTITAS ASI DENGAN PIJAT OKSITOSIN DAN TIDAK PADA IBU POST PARTUM - Vivi Silawati; Dedeh Saadah; Cholisah Suralaga (Universitas Nasional, 2020)
Objective : the research aims to identify the quantity of breast milk on postpartum mother with oxytocin massage and without oxcytocin massage. Methodology : this a Quasy Eksperiment study with post test only design. The sample in this study are 30 samples consisting of 15 experimental group which carried out oxytocin massage times 2 – 3 minutes and 15 control groups. The sampling technique in this study is purposive sampling. Data are analyzed using non – parametric test analysis (Anova). Research Result : the average expenditure of breast milk in the experimental group in the first 4 hour in 6.23 cc, the first 8 hours is 13,41 cc, and the first 12 hours is 19.72 cc. the average expenditure of breast milk in the control group in the first 4 hour 5.17 cc, first 8 hours is 10.9 cc, and the first 12 hours is 15.35 cc. there is an oxcytocin massage effect on breastmilk expenditure in puskesmas jatinegara in 2018 with P-value 0,000 (p-value < α(0,05)).